Neuroimaging in Superficial Siderosis: An In-Depth Look - Kumar, N. (American Journal of Neuroradiology, 2010)
SUMMARY: Despite extensive imaging, a source of bleeding is often not evident during the evaluation of patients with superficial siderosis (SS) of the central nervous system. An intraspinal fluid-filled collection of variable dimensions is frequently seen on spine MR imaging in patients with idiopathic SS. A similar finding has also been reported in patients with craniospinal hypotension. This review discusses the role of multitechnique imaging in the work-up of patients with SS and focuses on recent developments.